Free Flap Blood Flow Evaluated Using Two-Dimensional Laser Speckle Flowgraphy. (28th April 2011) - Furuta, Toshiaki; Sone, Michihiko; Fujimoto, Yasushi; Yagi, Shunjiro; Sugiura, Makoto; Kamei, Yuzuru; Fujii, Hitoshi; Nakashima, Tsutomu
Abstract : Objective . We investigated the efficiency of laser speckle flowgraphy for evaluating blood flow in free flaps used for plastic surgery. Methods . We measured blood flow using a visual laser meter capable of providing two-dimensional color graphic representations of flow distribution for a given area using a dynamic laser speckle effect. Using laser speckle flowgraphy, we examined the blood flow of 20 free flaps applied following the excision of head and neck tumors. Results . After anastomosis of the feeding and draining blood vessels and sewing the flap, musculocutaneous (MC) flaps showed significantly lower blood flow than jejunal or omental flaps (P < .05 ). The ratio of blood flow decrease from the edge to the center was significantly greater in MC flaps than in jejunal or omental flaps (P < .001 ). Conclusion . Laser speckle flowgraphy is useful for the perioperative measurement of blood flow in free flaps used in plastic surgery. This method is a highly useful, practical, and reliable tool for assessing cutaneous blood flow and is expected to be applicable to several clinical fields.